Buffering and enabling: The impact of interlocking political ties on firm survival and sales growth - Zheng, Weiting; Singh, Kulwant; Mitchell, Will (Strategic Management Journal, 2015)
Several studies suggest that political ties help firms survive or perform but do not examine the boundary conditions concerning which types of firms and which type of ties help firms. We draw from resource dependence and resource‐based theories to argue that political ties can improve both firm survival (labeled “buffering”) and performance (labeled “enabling”), with weaker firms gaining more from buffering and stronger firms gaining more from enabling. We further examine the relative impact of local and central ties. We test our hypotheses on the television manufacturing industry in China between 1993 and 2003. Results demonstrate the buffering roles of political ties, and under narrower conditions, their enabling roles. Local ties account for these outcomes, while central ties do not provide buffering or enabling benefits . Copyright © 2014 John Wiley & Sons, Ltd.